Air purifier – individual protection against indoor particulate matter - Chyc, Marek (Health Promotion & Physical Activity, 2020)
The research work presents the findings of testing air purified using two commercial air purifiers available on the local market. Tests were carried out in the office and bedroom of a residential building. The results obtained show a high (75–93%) yield of air purification from particulate matter. Particulate matters fractions such as: PM1, PM2.5, PM4.0, PM10 and total suspended particulates (TSP) were analysed by means professional dust meter. A very strong correlation of particulate matter (PM) contents were found in individual particle classes during equipment operation. Obtained results approve high efficiency of equipment operation in the total range of measured values. This study is one of the first in the topic of assessing the effectiveness of PM purification, taking into account various dust fractions. This study should be useful for individual customers and for public utilities during purchase decisions.